STRATEGI PEMBELAJARAN PAI BERBASIS INKUIRI DAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA - Sabarudin, Mohammad; Al Ayyubi, Ibnu Imam; Rohmatulloh, Rifqi (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2023)
This research is expected to provide stronger and more accurate evidence regarding the effectiveness of inquiry-based learning strategies in improving students' critical thinking skills. This research method uses correlation analysis to see the relationship between the independent variables, namely students' critical thinking and the dependent variable, namely student learning outcomes using the inquiry learning model in Islamic Religious Education courses. The population of this study were fifth semester students with a sample of 28 students at Darul Falah Islamic High School, West Bandung. Testing the requirements of the data analysis used consisted of a normality test and a linearity test with the hypothesis used, namely the correlation and regression tests. The results obtained in this study where there is a strong relationship between the independent variable and the dependent variable because the Correlation Coefficient value is 0.775 and is found in the interval 0.60-0.79 while the significance value of the Correlation is 0.000 which means there is a correlation between students' critical thinking and student learning outcomes using the model Inquiry learning in Islamic Religious Education courses.